30 CIMMYT advanced lines with high yield potential, good grain quality and disease resistance selected for national evaluation. - CGIAR Research Program on Wheat (2018)
30 CIMMYT advanced lines have been selected to complete broader testing under conditions intended to resemble those that the potential users will encounter.